STRATEGI PEMBERDAYAAN KELEMBAGAAN PETANI (Forum Penelitian Agro Ekonomi, 2016)
Decision making process among farmers is a community-based action which is viewed as an entry point of technology dissemination. Institutional empowerment has strong ties with farmer’s techno-social condition. Success in an empowerment program is a result of interaction among empowerment elements and the applied empowerment strategy. Empowerment effort and strategy is an overlapping pendulum of evolution-revolution paradigms in a proportion relevant to the farmer’s institutional condition and needs.
Keywords: community; institution; empowerment; komunitas; kelembagaan; pemberdayaan